Bortezomib-melphalan-prednisone versus lenalidomide-dexamethasone in elderly patients with multiple myeloma: the Real MM phase IV trial - Sara Bringhen; Lorenzo Cani; Nicola Giuliani; Silvia Mangiacavalli; Giulia Benevolo; Elisabetta Antonioli; Renato Zambello; Roberto Ria; Iolanda Donatella Vincelli; Sonia Ronconi; Sonia More; Antonietta Pia Falcone; et al. (Haematologica)
Not available.